Relationship of the Environment with Human Activities and Main Directions of Environmental Protection - N. M. Bakhriddinova (Open Academia, 2023)
The work examines the relationship between the environment and human activities and the main directions of environmental protection. The characteristics of air pollution in the working area are given. The main directions of strengthening environmental safety are widely covered.
Keywords: natural environment; human activity; relationship; environmental Safety